2005
DOI: 10.3233/bmr-2005-181-206
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of pain and disability in patients with chronic low back pain: Reliability and construct validity of the Turkish version of the Quebec Back Pain Disability Scale and Pain Disability Index

Abstract: Objectives: The objective of this study was to test the reliability and validity of the Turkish version of the Quebec Back Pain Disability Scale (QBPDS) and Pain Disability Index (PDI) as well as the retainment of the psychometric properties of the original versions. The importance of the region-specific functional measures on patients with chronic low back pain was also assessed. Methods: Eighty-three patients with chronic low back pain were enrolled in the study. The QBPDS, the PDI and The Hospital Anxiety a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
8
1
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 24 publications
(31 reference statements)
3
8
1
1
Order By: Relevance
“…Developed by Kopec et al in 1995 [3], it has ever since been used in many studies [4e7] and translated into several languages (Iranian [8], Dutch [9], French [10], and Turkish [11]). Its good measurement properties (reproducibility and validity) have been reported [1e3, 8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Developed by Kopec et al in 1995 [3], it has ever since been used in many studies [4e7] and translated into several languages (Iranian [8], Dutch [9], French [10], and Turkish [11]). Its good measurement properties (reproducibility and validity) have been reported [1e3, 8,9].…”
Section: Introductionmentioning
confidence: 99%
“…The SC-QDS internal consistency was excellent, with the Cronbach a reaching 0.976, higher than that of all other versions: original (0.96) [9], Dutch (0.95) [17], Iranian (0.92) [19], Brazilian (0.97) [20], Turkish (test, 0.941 and retest, 0.957) [21,22], Polish (0.95) [23], and Korean (0.92) [24]. It was noteworthy that the SC-QDS Cronbach a was limited to a very small range (0.974e0.976) if an item was deleted.…”
Section: Discussionmentioning
confidence: 70%
“…The summed total score indicates disability extent, ranging from 0 (no disability) to 100 (maximal disability). The QDS has been successfully adapted for measuring LBP impairment in several different cultural and language groups, including Dutch [17], French [18], Iranian [19], Brazilian [20], Turkish [21,22], Polish [23], and Korean [24]. However, no validated SC-QDS version has been reported.…”
Section: Introductionmentioning
confidence: 99%
“…In the study of Biçer et al 25 in Turkey, Cronbach's alpha of the PDI was found to be 0.84. However, our investigation is characterized by more reliable and generalizable results thanks to our larger sample size (212 participants in our study versus 83 in Biçer's study), higher item total correlation, and inclusion of a variety of musculoskeletal diseases that cause chronic pain; whereas in Biçer's study, the sample consisted of patients with low back pain.…”
Section: Discussionmentioning
confidence: 94%